Anathema in lateinischen Inschriften - Ehmig, Ulrike; Zawadzki, Konrad (Vox Patrum, 2019)
A recently finished study of early Christian epitaphs that contain the term adiuro or coniuro to protect the tombs shows that ignoring these instructions would be penalized with a series of draconian punishments. Relevant curses and punitive formulas were borrowed from the Old and New Testaments. Inter alia the culprit should be punished by means of anathema, the eternal damnation. In recent years Konrad F. Zawadzki has intensively dealt with anathema in the literary sources of the early church and pointed out that the punishment was used in doctrinaire disputes against heretics. The use of the term in Latin inscriptions, which has not been studied so far, is the focus of this study. The eleven relevant inscriptions dating from the 6th to the 8th century are analyzed epigraphically and theologically. They are directed against moral offenses and point to a later expansion and popularization of the meaning of anathema.